PERBANDINGAN DAN PENILAIAN PEMELIHARAAN FASAD CW DAN ACP BANGUNAN GEDUNG TERHADAP PERMEN PU NO.24/PRT/M/2008 - Imam Alfianto, Indah Lestari (BANGUNAN, 2022)
Abstract : Façade maintenance is often neglected and seems imprecise due to many factors, one of which is the location of the facade which is quite difficult to reach. Whereas maintenance on the facade is very important because the facade is the earliest part that is seen from a building and becomes a characteristic of the building, the maintenance applied should not be modest, but must be optimal and heed the relevant regulations. This study reviews by comparing and assessing the maintenance of the facade of the curtain wall material and aluminium composite panel with the Minister of Public Works Regulation No. 24/PRT/M/2008. Data collection methods used are interviews and questionnaires and to analyse using qualitative descriptive methods and percentages. From this method, it is possible to investigate the comparison of procedures in the field with procedures based on Permen PU No.24/PRT/M/2008 and the level of conformity of the procedures under review. Based on the results of the comparative analysis, the two procedures have similarities and differences, the procedures in the field as a whole are not in accordance with the procedures for the Minister of Public Works No. 24/PRT/M/2008, but the procedures in the field also have their own advantages. Based on the assessment, the level of conformity of the procedures in the field with the Minister of Public Works No. 24/PRT/M/2008 overall reached 86.64%. Meanwhile, based on the grouping of respondents, the score was 66.17% for group I, 78.95% for group II and 91.14% for group III. The overall results stated that the maintenance carried out was not fully in accordance with the regulations, but the results obtained showed good results, where the percentage obtained was more than 50%, this indicates that more than half of the maintenance was carried out by heeding the regulations. Keywords : Maintenance, Facade, Curtain Wall, Aluminum Composite Panel.